Fan spread effects at lower secondary school? The effect of school type on achievement gains in German and mathematics - Angelone, Domenico (Swiss Journal of Educational Research, 2019)
Applying Propensity Score Matching this longitudinal study (N = 950) examines whether comparable students achieve different achievement gains depending on the school type attended. The results show increasing achievement disparities as a result of school type specific achievement gains. Therefore additional effects of the school structure at lower secondary level exist, beside the known effects of origin on achievement gains in the early school years.